Contingent versus unconditional incentives in www-studies - Göritz, Anja S. (Metodološki zvezki, 2005)
Five experiments examined how participation in WWW-studies was influenced by framing the reception of an incentive as contingent on the completeness of the submitted questionnaire. Four experiments were carried out in a university-based online panel and one in a market research online panel. Four times the incentive was a prize draw and once it was a personal gift. In each experiment, two conditions were contrasted: one group received an e-mail invitation mentioning that all participants are eligible for the incentive (= unconditional incentive), whereas the other group was told that only those participants who answer every question in the questionnaire would receive the incentive (= contingent incentive). Dependent measures were response rate, retention rate, number of omitted closed-ended items, length of answers to open-ended questions, and stereotypical answering of grid-like question batteries. There were no significant effects. The results of the individual experiments were then meta-analytically aggregated. It was revealed that contingent relative to unconditional incentives decrease response to a study, while at the same time the sparser data are not compensated for by a superior data quality or retention.
Keywords: Internet; Družboslovno raziskovanje; svetovni splet